OP0180 Maintenance of Efficacy by Canakinumab Treatment in Systemic Juvenile Idiopathic Arthritis Patients. (10th June 2014) - Wulffraat, N.M.; Ruperto, N.; Brunner, H.I.; Oliveira, S.; Uziel, Y.; Nistala, K.; Cimaz, R.; Ferrandiz, M.A.; Flato, B.; Gamir, M.L.; Koné-Paut, I.; Gaillez, C.; et al.
Abstract : Background: Systemic juvenile idiopathic arthritis (SJIA) is characterized by recurrent flares of active disease comprising of fever, arthritis and markedly elevated inflammatory markers. Canakinumab (CAN), a fully human, selective, anti-IL-1β monoclonal antibody was approved for SJIA patients (≥2 years old) by over 30 countries including USA, EU, Russia and Canada. CAN treatment in patients with SJIA allows for successful steroid dose reduction/discontinuation and reduces risk to experience a flare. 1 Objectives: To evaluate the maintenance of efficacy with continued CAN treatment in SJIA patients during the blinded randomized treatment withdrawal part of a large phase III trial. Methods: Patients 2–19 yrs of age with active SJIA who had responded to open-label CAN treatment 4mg/kg/4wks sc, maintained a minimum adapted ACR Pediatric criteria [aACR] 30 for up to 32 weeks, and were steroid-free or had successfully reduced systemic steroids to a minimum dose, were randomized to either continue CAN or receive placebo until 37 flare events occurred. 1 Patients were considered to have completed the study if they entered clinical remission on medication (CRM), i.e. achieved 24 consecutive weeks of clinical inactive disease (CID). 2 A survival analysis of the time to worsening in aACR level, after randomization for the CAN and placebo groups was performed. Time to worsening is the time to fail to maintain at least the same level of ACR response seen at randomization. The change in the proportion in each group of those with CID was also evaluated. Results: 100 pts were randomized to a CAN (n=50) or a placebo (n=50) group, of whom 26 (53%) and 27 (54%), respectively, had CID at the start of the randomization part. In the first 2 months, probability of maintaining aACR response was similar for both treatment groups. Thereafter, the probability of maintaining aACR response was greater in the CAN vs. placebo groups. The median time to worsening in aACR level for patients in the placebo group was 141 days (95% CI: 85, 281), and could not be calculated for CAN as <50% of CAN group had a worsening in their aACR level by the end of this phase. The median duration of exposure for the CAN group was 221.5 days (range: 8-617 days). There was a statistically significant relative risk reduction of 51% for the CAN vs. placebo group to experience a worsening in aACR level (HR=0.49; 95% CI: 0.27, 0.90; p=0.0131). CID was achieved by 31 (62.0%) vs. 17 (34.0%) patients in CAN vs placebo group at their last visit (OR=3.4; 95% CI: 1.5, 8.0; p=0.0020) and CRM was reached by 20 (40%) CAN and 2 (4%) placebo pts by the end of the study. Conclusions: A greater proportion of SJIA pts who continued CAN treatment maintained/improved their aACR response, achieved CID and CRM than pts who discontinued CAN by being switched to placebo, demonstrating maintenance of efficacy with continued CAN treatment over time. References: Ruperto N, et al. N Engl J Med 2012;367(25):2396–406. Wallace CA, J Rheumatol 2004;31(11):2290-4 Disclosure of Interest: N. Wulffraat Grant/research support: Abbvie, Roche, Consultant for: Novartis, Pfizer, Roche, N. Ruperto Grant/research support: To Gaslini hospital from Abott, Astrazeneca, BMS, Centocor reserach& development, Eli lilly & company, "Francesco Angelini", Glaxo Smith & Kline, Italfarmaco, Novartis, Pfizer Inc., Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth Pharmaceuticals Inc., Speakers bureau: Astrazeneca, Bristol Myers and Squibb, Janssen Biologics B.V., Roche, Wyeth, Pfizer, H. Brunner Consultant for: Roche, Janssen, Novartis, Astrazeneca; UCB, Celegene, Pfizer, GSK, Speakers bureau: Novartis, S. Oliveira Grant/research support: Novartis, Roche, Y. Uziel Speakers bureau: Fee for few talks at medical meeting from Novartis, Neopharm, Roche, K. Nistala: None declared, R. Cimaz: None declared, M. Ferrandiz Grant/research support: Principal investigator fees by Novartis, B. Flato Grant/research support: Coinvestigator in the initial study on efficacy by canakinumab treatment in systemic juvenile idiopathic arthritis patients. Expenses for personnel covered by Novartis, M. Gamir: None declared, I. Koné-Paut Grant/research support: SOBI, LFB, Consultant for: Novartis, SOBI, Pfizer, Chugai, C. Gaillez Employee of: Novartis Pharma AG, K. Lheritier Shareholder of: Novartis, Employee of: Novartis Pharma AG, K. Abrams Shareholder of: Novartis, Employee of: Novartis Pharmaceutical corporation, A. Martini Grant/research support: From Bristol Myers and Squibb, Centocor Research & Development, Glaxo Smith to Gaslini hospital for PRINTO research activities, Consultant for: From Bristol Myers and Squibb, Centocor Research & Development, Glaxo Smith & Kline, Novartis, Pfizer Inc, Roche, Sanofi Aventis, Schwarz Biosciences GmbH to Gaslini hospital for PRINTO research activities, Employee of: Gaslini hospital, Speakers bureau: Abbott, Bristol MyersSquibb, Astellas, Boehringer, Italfarmaco, MedImmune, Novartis, NovoNordisk, Pfizer, Sanofi, Roche, Servier, D. Lovell Grant/research support: National Institutes of Health- NIAMS, Consultant for: Astra-Zeneca, Centocor, Amgen, Bristol Meyers Squibb, Abbott, Pfizer, Regeneron, Roche, Novartis, UCB, Forest Research Institute, Horizon, Johnson & Johnson, Speakers bureau: Novartis, Roche DOI: 10.1136/annrheumdis-2014-eular.1215